MEMBANGUN KARAKTER BANGSA MELALUI CERITA RAKYAT NUSANTARA (MODEL PENDIDIKAN KARAKTER UNTUK ANAK MI AWAL BERBASIS CERITA RAKYAT DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN ISLAM) - Fulan (Jurnal Pendidikan Agama Islam, 2012)
The age of children is the gold age period, where is the system of nerve has achieved 100-200 billion and its intelligence has achieved 80 %. This age is a period that the most appropriately for giving education servicing adequately. One of them is building the character. This article discuss character developmenting through folklore with educational pscychology and socio-antrophology approaches. Folklore, in order to socio-antrophology more able to received causes of appropriately by the culture of nation. Besides of, in psychology folklore more able to received by children causes of also appropriately with the cognitive developmenting that riches of imagination. The result of this discuss shows if developmenting the children character may be done through folklore with basing local wisdom in global era like now. But, folklore gets two big challenges namely irriasional modern era and pointing belief in more than of Gog (syirik) or polytheism in Islam. That is why it is necessary to divepeloped to be more scientific modern an relegious one.